Re-conceptualizing sustainable urban sanitation in Uganda: why the roots of 'Slumification' must be dealt with - Japheth Nkiriyehe Kwiringira; Robert Kabumbuli; Henry Zakumumpa; James Mugisha; Mathias Akugizibwe; Paulino Ariho; Joseph Rujumba (BMC, 2021)
Abstract Background Country-wide urbanization in Uganda has continued amidst institutional challenges. Previous interventions in the water and sanitation sector have not addressed the underlying issues of a poorly managed urbanization processes. Poor urbanisation is linked to low productivity, urban poverty, unemployment, limited capacity to plan and offer basic services as well as a failure to enforce urban standards. Methods This ethnographic study was carried out in three urban centres of Gulu, Mbarara and Kampala. We explored relationships between urban livelihoods and sustainable urban sanitation, using the economic sociology of urban sanitation framework. This framework locates the urbanization narrative within a complex system entailing demand, supply, access, use and sustainability of slum sanitation. We used both inductive and deductive thematic analysis. Results More than any other city in Uganda, Kampala was plagued with poor sanitation services characterized by a mismatch between demand and the available capacity for service provision. Poor slum sanitation was driven by; the need to escape rural poverty through urban migration, urban governance deficits, corruption and the survival imperative, poor service delivery and lack of capacity, pervasive (urban) informality, lack of standards: 'to whom it may concern' attitudes and the normalization of risk as a way of life. Amidst a general lack of affordability, there was a critical lack of public good conscience. Most urbanites were trapped in poverty, whereby economic survival trumped for the need for meeting desirable sanitation standards. Conclusions Providing sustainable urban livelihoods and meeting sanitation demands is nested within sustainable livelihoods. Previous interventions have labored to fix the sanitation problem in slums without considering the drivers of this problem. Sustainable urban livelihoods are critical in reducing slums, improving slum living and curtailing the onset of slumification. Urban authorities need to make urban centres economically vibrant as an integral strategy for attaining better sanitation standards.